Soil loss in the wachado old system in the upper tropics of Nariño, Colombia - Volveras-Mambuscay, Belisario; Merchancano-Rosero, José Domingo; López-Rendón, Juan Fernando; Campo-Quesada, José Manuel (Agronomía Mesoamericana, 2021)
Introduction. The ancestral wachado (furrow or ridge) system, used on the slopes of Nariño for the production of potatoes and milk, does not use heavy machinery and has less impact on soil productivity. Objective. To evaluate the furrow inclination adjustment of the furrow for potatoes and its effect on soil loss in the high Andean zone of Nariño. Materials and methods. The work was carried out in the towns of Pasto, Potosí, and Pupiales between May and October 2014. A complete randomized block design with three repetitions and four treatments (wachado at 90°, 70°, 60°, and commercial tillage) was used. Gutters were built at the base of each experimental unit to collect the displaced soil. Soil loss and tuber yield were evaluated. Results. A significant effect of furrow inclination on soil loss was observed; the highest total loss of soil was obtained in furrows in the direction of the slope (90°) with an average of 69.29 t ha-1 for commercial tillage and 63.51 t ha-1 for wachado; the lowest loss was 45.76 t ha-1 in wachado at 60°. Of the total loss of soil, the highest proportion occurred in the first two months of cultivation, which included sowing and hilling; 90 %, 60 %, and 67 % were lost in these tasks for Pasto, Potosí, and Pupiales, respectively. No furrow inclination effect was observed on potato yield, which reached an average of 44.94 t ha-1. Conclusion. The furrows inclination reduction diminished the soil loss during the cultivation cycle without affecting the yield and it is suggested to validate it at a commercial level since it could contribute to the reduction of soil degradation in the Andean slopes of Nariño.